Reduced nicotine in cigarettes in a marketplace with alternative nicotine systems: randomized clinical trialResearch in context - Dorothy K. Hatsukami; Joni A. Jensen; Dana Mowls Carroll; Xianghua Luo; Lori G. Strayer; Qing Cao; Stephen S. Hecht; Sharon E. Murphy; Steven G. Carmella; Rachel L. Denlinger-Apte; Suzanne Colby; Andrew A. Strasser; et al. (Elsevier, 2024)
Summary: Background: Reducing cigarette addictiveness has the potential to avert millions of yearly tobacco-related deaths worldwide. Substantially reducing nicotine in cigarettes decreases cigarette consumption, but no large clinical trial has determined the effects of reduced-nicotine cigarettes when other nicotine-containing products are available. The aim of this study was to examine the effects of reduced-nicotine cigarettes in the context of the availability of alternative nicotine delivery systems. Methods: In a U.S. six-site, open-label, parallel-arm study, smokers were randomized for twelve weeks to an experimental marketplace containing cigarettes with either 0.4 mg or 15.8 mg nicotine per gram of tobacco; all had access to non-combusted alternative nicotine delivery systems (e.g., e-cigarettes; medicinal nicotine). Group differences in the primary outcomes (cigarettes per day, number of smoke-free days) were examined using linear and negative binomial regression, respectively (Trial Registration: NCT03272685). Findings: Among 438 randomized participants (mean [standard deviation (SD), range] age, 44.5 [11.9, 20-73] years, 225 [51.4%] women, 282 [64.4%] White and 339 [77.4%] trial completers), those in the 0.4 mg vs. 15.8 mg nicotine cigarette condition experienced significantly lower cigarettes per day at the end of intervention (mean [SD], 7.05 [7.88] vs. 12.95 [9.07], adjusted mean difference, −6.21 [95% CI, −7.66 to −4.75], P < 0.0001) and greater smoke-free days during intervention (mean [SD], 18.59 [27.97] vs. 5.06 [13.77], adjusted rate ratio, 4.25 [95% CI, 2.58-6.98], P < 0.0001). Interpretation: A reduced-nicotine cigarette standard in the context of access to other non-combusted nicotine products has the potential to benefit public health. Funding: U.S. NIH/FDA U54DA03165.